The Regulation of Light Sensing and Light-Harvesting Impacts the Use of Cyanobacteria as Biotechnology Platforms - Montgomery, Beronda L. (Frontiers in Bioengineering and Biotechnology, 2014)
Light is harvested in cyanobacteria by chlorophyll-containing photosystems embedded in the thylakoid membranes and phycobilisomes (PBSs), photosystem-associated light-harvesting antennae. Light absorbed by the PBSs and photosystems can be converted to chemical energy through photosynthesis. Photosynthetically-fixed carbon pools, which are constrained by photosynthetic light capture versus the dissipation of excess light absorbed, determine the available organismal energy budget. The molecular bases of the environmental regulation of photosynthesis, photoprotection and photomorphogenesis are still being elucidated in cyanobacteria. Thus, the potential impacts of these phenomena on the efficacy of developing cyanobacteria as robust biotechnological platforms require additional attention. Current advances and persisting needs for developing cyanobacterial production platforms that are related to light sensing and harvesting include the development of tools to balance the utilization of absorbed photons for conversion to chemical energy and biomass versus light dissipation in photoprotective mechanisms. Such tools can be used to direct energy to more effectively support the production of desired bioproducts from sunlight.